2018
DOI: 10.1038/s41598-018-29291-z
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates persistence of Acinetobacter baumannii against colistin

Abstract: Persisters are phenotypic variants of normal susceptible bacterial populations that survive prolonged exposure to high doses of antibiotics and are responsible for pertinacious infections and post-treatment relapses. Out of the three antibiotics, Acinetobacter baumannii formed the highest percentage of persister cells against rifampicin followed by amikacin and the least against colistin. Colistin-treated cells formed the high levels of reactive oxygen species (ROS) whose quenching with bipyridyl and thiourea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…ROS generation in A. baumannii was assayed as described previously [39]. Briefly, overnight grown cells of A. baumannii ATCC 17978 in TSB were harvested, washed and re-suspended at 10 6 CFU/mL in PBS.…”
Section: Reactive Oxygen Species (Ros) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…ROS generation in A. baumannii was assayed as described previously [39]. Briefly, overnight grown cells of A. baumannii ATCC 17978 in TSB were harvested, washed and re-suspended at 10 6 CFU/mL in PBS.…”
Section: Reactive Oxygen Species (Ros) Assaymentioning
confidence: 99%
“…To understand the mechanism responsible for 5-iodoindole induced cell death, we first investigated its effects on membrane integrity using colistin as a positive control, which has been reported to induce surface roughness and disrupt membrane integrity [39]. SEM analysis showed obvious cell shrinkage after treatment with 5-iodoindole at 125 µg/mL for 60 min ( Figure 5 and Figure S4).…”
Section: -Iodoindole Killing Of a Baumannii Was Mediated By Cell Mementioning
confidence: 99%
“…In addition to the widespread of drug resistance, A. baumannii persistence also contributes to the treatment failure even at high doses of antibiotics [20]. Despite the endeavours have been made to understand the persistence and its eradication [21][22][23][24], the mechanism for persistence formation in A. baumannii is yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, also known as diferuloylmethane, E100 or natural yellow 3 (International Union of Pure and Applied Chemistry (IUPAC) name is (1E, 6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione, Figure 1 b), is a natural polyphenol extracted from the rhizome of Curcuma longa [ 39 ]. Curcumin displays many beneficial pharmacological actives, such as anti-inflammatory, anti-oxidant, antitumor and notably, antimicrobial activities [ 24 , 40 , 41 , 42 , 43 ]. The direct antibacterial activities of curcumin have been widely studied [ 44 , 45 ].…”
Section: Curcuminmentioning
confidence: 99%
“…Natural products have been the source of most of our antibacterial armamentarium and efforts over the last 30 years [ 22 ]. Recent studies have shown that combining polymyxins with curcumin has many pharmacological and toxicological benefits over monotherapy with each compound per se including: (1), the in vitro synergy against various strains of MDR bacteria [ 23 ], including polymyxin resistant isolates [ 24 ]; (2), protection against polymyxin-induced nephron- and neuro-toxicity [ 25 , 26 , 27 ]; (3), curcumin supplementation improves recovery from the bacterial infection or LPS—induced inflammatory response or sepsis [ 28 , 29 , 30 , 31 , 32 , 33 ]. Importantly, human clinical trials indicated that curcumin displays good safety and tolerability [ 34 , 35 , 36 ]; oral administration of curcumin at eight grams per day over three months or a single oral dose of 12 grams has no marked adverse effect [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%